The implicit costs and benefits of family friendly work practices - John S. Heywood; William Stanley Siebert; Xiangdong Wei (Institute for the Study of Labor (IZA), 2005)
This paper posits that the provision of family friendly practices is, on balance, costly to firms and valuable to workers. As a consequence, we anticipate the emergence of a hedonic equilibrium in which workers provided with such practices face an implicit reduction in their earnings. Using WERS98 linked employer-employee data, we show that the ability to confirm this compensating wage differential depends critically on an appropriate treatment model designed to purge typical estimates of the income effect. We find that family friendly jobs may be associated with as much as a 20 percent reduction in earnings. Our estimates can be used to inform impact assessments of new UK legislation extending family friendly practices.
Keywords: 330; family friendly work practices; hedonic equilibrium; compensating wage differential; legislative impact assessment; Flexible Altersgrenze; Arbeitslosigkeit; Einkommensverteilung; Gini-Koeffizient; Schätzung; Belgien